Manajemen Evaluasi (Muhasabah) Diri - Eka Ariska Wanti; Subiyantoro Subiyantoro (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
The research was carried out with the aim of discussing evaluation management (self-reflection). Muhasabah is a medium for self-improvement, self-introspection, and a belief in reckoning actions against oneself before the reckoning is carried out by Allah SWT. The research method used is the method of literature study / study research. The data collection method is done by summarizing, reading, taking notes, understanding, and studying various literatures that are in line with the research theme. The research resulted in the presentation of: 1) evaluation (supervision) of the perfect management of the Qur'an and Hadith, 2) the basis of self-evaluation management (muhasabah) in the perspective of the Qur'an and Hadith, 3) the last discussion regarding the implementation of self-evaluation. (muhasabah) management perspective, the following management efforts are carried out in muhasabah management, namely: 1) planning (planning) in muhasabah management. Planning muhasabah is aimed at building character values, considering actions, and improving worship (spiritual values) towards Allah SWT. These efforts come from a positive heart and mind. 2) organizing in muhasabah management. The purpose of organizing efforts in muhasabah is more directed to setting habits / tips to improve oneself. Then 3) implementation (acting) in muhasabah management. The purpose of implementing muhasabah management is the implementation of muhasabah efforts that have been planned on the basis of good planning and time management. And 4) controlling or controlling in muhasabah management. Evaluation means knowing how far, or how optimally the effort is carried out.